Establishment of two new human bladder carcinoma cell lines, CAL 29 and CAL 185. Comparative study of cell scattering and epithelial to mesenchyme transition induced by growth factors - Cattan, N (Nature Publishing Group, 2001)
We describe here two new human urothelial carcinoma cell lines, CAL 29 and CAL 185, established from two patients with high-grade tumours and which display very different properties in vitro. We have shown that CAL 29 cells were tumorigenic in mice and expressed characteristic features of both cell scattering and transition from epithelial to mesenchymal phenotype (EMT) after triggering by the EGF receptor ligands, TGFα and EGF. At the opposite, the CAL 185 cells were not tumorigenic in mice and neither scattered nor expressed vimentin intermediary filaments in the presence of growth factors. We further demonstrated that CAL 29 cell scattering was reversible after growth factor removal and that both scattering and EMT were markedly impaired after treatment with MEK, Src and PI3-kinase inhibitors suggesting that these kinases might be important components of the cellular responses to EGF and TGF-α leading to scattering and EMT. These agents could help to understand the intracellular pathways involved in invasiveness and to find new targets for limiting metastasis. In conclusion, these two new cell lines could be good models to dissect the molecular mechanisms involved in invasion and metastasis development in human bladder cancer. © 2001 Cancer Research Campaign  http://www.bjcancer.com